Roles of individual employees in the management of employment records in Kilwa district council - Mvulla, Adolphina L. (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management in partial fulfilment of the requirements for award of the degree of Master of Science in Human Resource Management(MSc-HRM) of Mzumbe University